THE ROLE OF FAMILY COMMUNICATION IN CHILDREN’S LANGUAGE DEVELOPMENT A PSYCOLINGUISTIC A REVIEW - Hutapea, Dewi Kristina; Damanik, Bernieke Anggita Ristia (Sindoro: Cendikia Pendidikan, 2025)
This review explores the pivotal role of family communication in the language development of children, framed within a psycholinguistic context. Language acquisition is a complex process influenced by various factors, including the linguistic environment provided by family interactions. The study highlights how verbal exchanges, non-verbal cues, and the emotional tone of family communication contribute to children's vocabulary expansion, grammatical understanding, and overall communicative competence Key findings indicate that frequent, meaningful conversations between parents and children foster a richer language environment, promoting not only vocabulary growth but also cognitive skills and social-emotional development. The use of diverse linguistic inputs, such as storytelling and interactive play, is shown to enhance children's language skills significantly. Moreover, the role of parental responsiveness and encouragement in facilitating effective communication is emphasized This review underscores the importance of fostering healthy communication patterns within the family unit as a foundation for successful language development in children, suggesting implications for educational practices and interventions aimed at supporting language acquisition in early childhood.